2. a) Express \( \frac{\sqrt{3}+1}{\sqrt{3}-1}+\sqrt{3}-1 \) in the form \( a+b \sqrt{3} \) where \( a \) and \( b \) are rational numbers. b) Express \( \frac{5}{3-2 \sqrt{3}} \) in the form \( a+b \sqrt{3} \) where \( a \) and \( b \) are rational numbers.
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To tackle part a), we can start by rationalizing the expression \( \frac{\sqrt{3}+1}{\sqrt{3}-1} \). This is done by multiplying the numerator and the denominator by the conjugate of the denominator, \( \sqrt{3}+1 \): \[ \frac{(\sqrt{3} + 1)(\sqrt{3} + 1)}{(\sqrt{3} - 1)(\sqrt{3} + 1)} = \frac{(\sqrt{3} + 1)^2}{3 - 1} = \frac{3 + 2\sqrt{3} + 1}{2} = \frac{4 + 2\sqrt{3}}{2} = 2 + \sqrt{3} \] Now, adding \( \sqrt{3} - 1 \): \[ (2 + \sqrt{3}) + (\sqrt{3} - 1) = 2 + 2\sqrt{3} - 1 = 1 + 2\sqrt{3} \] So, the final form is: **Part a**: \( 1 + 2\sqrt{3} \). For part b), we rationalize the denominator of \( \frac{5}{3 - 2\sqrt{3}} \) by multiplying by the conjugate \( 3 + 2\sqrt{3} \): \[ \frac{5(3 + 2\sqrt{3})}{(3 - 2\sqrt{3})(3 + 2\sqrt{3})} = \frac{15 + 10\sqrt{3}}{9 - 12} = \frac{15 + 10\sqrt{3}}{-3} = -5 - \frac{10}{3}\sqrt{3} \] So, the final form is: **Part b**: \( -5 - \frac{10}{3}\sqrt{3} \).